PENGARUH PDRB (PRODUK DOMESTIK REGIONAL BRUTO) PERKAPITA DAN INFLASI TERHADAP PENJUALAN OTOMOTIF DI INDONESIA - Syari’udin, Akhmad (Media Ekonomi, 2018)
The development of autmotive Indonesia has a fairly rapid development so that many investors who do investment in the field of automotive in Indonesia. The development of automotive market in Indonesia is not only influenced by internal factors, but also influenced by external factors, both macro variable and micro variable. One of the macro variables affecting automotive development in Indonesia is the per capita GDP and the inflation rate of each automotive market region. This study aims to analyze the influence of per capita GDP and inflation rate on automotive sales based on 33 provinces in Indonesia. The methodology used is the regression of panel data with 33 provinces cross section and time series data in 2016. The results showed that: per capita GRDP per statistically and partially significant influence of automotive sales in 33 provinces of Indonesia while variable inflation rate is not significant at confidence level95%. Whereas at 95% level of confidence, both variables significantly affect automotive sales in Indonesia. In other word, is simultaneously, both the per capita GDP and inflation rate variables significantly influence automotive sales in 33 provincesof Indonesia. Thus, the automotive industry needs to pay attention to these two variables in developing its production sales and developing the market in 33 provinces of Indonesia. The Government of Indonesia, in doing the development of infrastructure should consider the growth of automotive sales in every province in Indonesia. Keywords: PDRB Percapita, Inflation Rate, Panel Data, Automotive Sales